PANDANGAN FIQIH TERHADAP INFAQ DALAM PEMBIAYAAN BERMASALAH DI KOPERASI SYARIAH MAN OKU TIMUR - Meriyati Meriyati; M Nasyah Agus Saputra Nasyah (Jurnal Istiqro, 2023)
This article examines members who can afford to pay dues on their loans in cooperatives. However, there are still many who have experienced a decline, because this cooperative is sharia-based, so as much as possible it does not apply fines to its members, but still provides a deterrent effect so that members do not underestimate the obligation to pay their loans and discipline from the cooperative administrators. So an agreement was held to implement infaq on the problematic financing of sharia cooperatives in MAN OKU East. The discussions that will be examined on the issues include the following: 1) The mechanism of sharia cooperatives of MAN OKU Timur in managing financing?, and 2) The implementation of infaq on problematic financing of sharia-based cooperatives in MAN OKU Timur ?. The research uses qualitative methods that are descriptive-qualitative with an approach with field and theoretical studies. The theories that can be used are: regarding financing, and sharia cooperatives. The research is carried out through the data collected as follows: observing and interviewing, as well as documenting the research, The results of this study show that the implementation of infaq substitutes for fines in the MAN OKU Timur sharia cooperative in dealing with arrears of problematic financing has not been maximized, due to the absence of a strong commitment for members in responding to the regulation, it can be concluded that there are still many problems that have not been resolved, as for handlers on problematic financing. Thus, it can be said that the sharia cooperative MAN OKU East, has not been able to implement infaq as a handler of problematic financing appropriately and has not carried out management management based on joint commitments to the fullest. However, in Islamic fiqih law, the system of handling the application of infaq is in accordance with the law of fiqih.